2001
DOI: 10.1364/ao.40.002675
|View full text |Cite
|
Sign up to set email alerts
|

Photometric methods for determining the optical constants and the thicknesses of thin absorbing films: selection of a combination of photometric quantities on the basis of error analysis

Abstract: We select the best combinations of spectrophotometric quantities for the most accurate determination of the optical constants, n (refractive index), k (absorption coefficient), and the thicknesses of thin absorbing films. The basic comparative criteria used are the maximum absolute errors in the determination of n, k, and d that result from experimental errors in photometric measurements and in the optical constants of the substrates. We studied all possible combinations of photometric quantities T, T(s)(theta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…We have demonstrated that the spectrophotometric and ellipsomeric methods offer a good accuracy for determination of the optical parameters of thin chalcogenide films from /30 to 2 ( is working wavelength) (Konstantinov et al 1998, Babeva et al 2001, Todorov et al 2010a. Results on the reflectance response of photonic crystals from chalcogenide glass/polymer (DeCorby et al, 2005;Kohoutek et al, 2007a) or chalcogenide glass/chalcogenide glass, e.g.…”
Section: Optical Methods For Control and Characterization Of Thin Filmentioning
confidence: 99%
See 1 more Smart Citation
“…We have demonstrated that the spectrophotometric and ellipsomeric methods offer a good accuracy for determination of the optical parameters of thin chalcogenide films from /30 to 2 ( is working wavelength) (Konstantinov et al 1998, Babeva et al 2001, Todorov et al 2010a. Results on the reflectance response of photonic crystals from chalcogenide glass/polymer (DeCorby et al, 2005;Kohoutek et al, 2007a) or chalcogenide glass/chalcogenide glass, e.g.…”
Section: Optical Methods For Control and Characterization Of Thin Filmentioning
confidence: 99%
“…8. The Swanepoel's method (Swanepoel, 1983) was used for optical constants determination of the thin films with d > 300 nm and a combination of double (T, R) and triple (T, R, R) methods was applied in calculations for thinner layers (d < 300 nm) (Konstantinov et al, 1998;Babeva et al 2001). The calculated values for optical parameters of thin films show that their refractive index is independent on the layer's thickness for d > 50 -70 nm (Fig.…”
Section: Optical Properties Of Thin Chalcogenide Filmsmentioning
confidence: 99%
“…Such treated samples show a "layer-like" structure [17]. Then an averaging method [18,19] to analyse effective optical properties of modified materials can be justified. Such method allows for characterisation of the bulk and the surface when the samples are not too thick and absorbing.…”
Section: Analysis Of Absorbing Structuresmentioning
confidence: 99%
“…These include the principal angle of incidence / principal azimuthal angle method [1,2], reflectance of plane polarized light at non-normal incidence [3] pseudo-polarizing angle method [4] and ellipsometric measurements [5,6]. Other techniques include interferometric, reflectance, photometric and other methods [7][8][9].…”
Section: Introductionmentioning
confidence: 99%